Ecosystem Organization of a Complex Landscape: long-term research in the Bornhöved Lake District, Germany - Fränzle, Otto. (Springer, 2017)
General concept of the research programme and methodology of investigations -- Ecological setting of the study area -- Ecophysiological key processes in agricultural and forest ecosystems -- Carbon and energy balances of different ecosystems and ecosystem complexes of the Bornhöved Lake District -- Weather relations at different scales -- Site-related biocoenotic dynamics -- Biocoenotic interactions between different ecotopes -- Element fluxes in atmosphere, vegetation and soil -- Transport processes between Lake Belau and its drainage basin -- Lake Belau -- Ecological gradients as causes and effects of ecosystem organization -- An indicator-based characterization of the Bornhöved key ecosystems -- Ecosystem research and sustainable land use management -- Conclusions : perspectives for integrative landscape planning, management and monitoring -- References -- Index.